Optimizing Smallholder Farmers' Productivity Through Crop Selection, Targeting and Prioritization Framework in the Limpopo and Free State Provinces, South Africa - Kephe, Priscilla Ntuchu; Siewe, Lendeu Constantain; Lekalakala, Ratunku Gabriel; Kwabena Ayisi, Kingsley; Petja, Brilliant Mareme (Frontiers in Sustainable Food Systems, 2022)
Smallholder farmers like those in Limpopo and the Free State (FS) Province of South Africa sometimes incur high production costs due to their crop choices. This cost is exacerbated by the challenges posed by climate change and the socio-economic position of the smallholder farmers. The opportunity cost of producing cost-intensive crops is the forgone benefits these smallholder farmers would have gained if they grew cheaper options. Therefore, a tool to assist farmers and stakeholders when choosing, advising on, or assisting with production and management decisions at farm levels to ensure profitability and sustainability is needed. This paper aimed at providing a framework to assist farmers in identifying profitable crops for production under the present day and possible future scenarios in Limpopo and the FS. This framework uses a multi-stage process with forward and backward linkages to refine analysis and results. Through reviews, interviews, focus groups and transect walks, the state of the biophysical, socio-economic, and political environment and their impact on smallholder farming were collected from 600 farmers and 40 key informants. Inferential statistics and cost-benefit analysis were used for data analysis. The results indicate that maize, though widely cultivated in both Provinces, has the highest average total production cost of R 29,694.39 /ha while the lowest was sunflower with R 6,453.78 /ha. Irrigated maize had the highest break-even price per hectare of R 38 351.85, while sunflower had the lowest R 4 685.85. In both provinces, groundnut ranked first on Net Present Value (NPVs) at discount rates of 8% and 10%, while low yield maize ranked last, scoring values of –R 4 163 894 and –R 3 953 393. Groundnut had the highest Benefit Cost Ratio (BCR) at 2.22 and 6.70 in Limpopo and FS. The BCR for low-yield maize was the lowest of all the crops. The base scenario results in economic and financial terms indicate it is better to farm sunflower, soybean, grain sorghum, and groundnuts than maize because of lower production cost and maize substitutes. Furthermore, climate change projections suggest a drier future for these provinces, implying the yield targets for farmers producing maize would be difficult to achieve when faced with climate change. Such information is vital for stakeholders.